Comparison of Black Orchid (Coelogyne pandurata Lind.) Subculture with the Addition of Leaf Fertilizer and Natural Tomato-Potato Extract - Faradilla; Nur Hidayat; Adelia Juli Kardika (Jurnal Loupe, 2025)
Black orchids are a renowned germplasm source in East Kalimantan. However, their habitat is becoming increasingly scarce due to slow cultivation, necessitating rapid and precise propagation methods, such as tissue culture. Subculture is a key component of tissue culture. The purpose of this study was to determine the growth response of black orchid on MS growing media with the addition of foliar fertilizer and natural extracts.  This research was conducted at the Tissue Culture Laboratory, Faculty of Mathematics and Natural Sciences, Mulawarman University. The study period was three months, from March to June 2025. This study used a non-factorial Completely Randomized Design (CRD). Three treatment levels, each level consisting of eight replications: S0 (control), S1 (MS Media + leaf fertilizer), S2 (MS Media + natural extract). Data were analyzed for diversity using Analysis of Variance (ANOVA) with an α level of 5% and then Duncan's Multiple Range Test (DMRT) with an α level of 5%. The results showed that all three treatments significantly affected all observed variables. The addition of leaf fertilizer to MS media produced the best response in terms of shoot emergence time and shoot number. The addition of natural extract to MS media produced the best response in terms of leaf number.